Sexual Self-Disclosure: A Study on Communication Behaviors among Users in Online Dating Applications - Puspita Sari Sukardani; Anam Miftakhul Huda; Farid Pribadi; Sueb Sueb; Anggaunitakiranantika Anggaunitakiranantika (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
The development of digital technology has changed the way people communicate. The existence of online media is no longer a medium of information but also has become a space for human interpersonal relationships. One of the phenomena is the shifted pattern of a group of people looking for a life partner virtually through dating applications. This emerging trend of online dating applications in the vast digital world has been contradicted with the values of the Eastern community including Indonesia. The communication pattern employed by the users, despite it being considered taboo to some extent, includes the sexual self-disclosure by users to targeted partners in the online dating apps. The study aims at understanding the process of communication of sexual self-exposure by the users in the online dating application. Additionally, this study examines how sexual behaviors as the implication of online interactions. There are some dynamics employed in sexual self-disclosure in the process of online communication, factors that influence the way to communicate in the online dating apps, including occupation, recent events, and sexual experiences